Pengaruh Good Corporate Governance pada Kinerja LPD dengan Budaya Organisasi Berorientasi Tim sebagai Variabel Mediasi - Darmayanti, Ni Putu Gita; Dwi Ratnadi, Ni Made; Aryista Dewi, Ayu; Wirawan Yasa, Gerianta (E-Jurnal Akuntansi; Vol 30 No 10 (2020)DO - 10.24843/EJA.2020.v30.i10.p03, 2020)
This research was aims to obtain to empirical evidence of the influence of GCG on the performance of LPD, the effect of GCG on team-oriented organizational culture, the influence of team-oriented organizational culture on LPD performance, examine the culture of team-oriented organizations as mediating the relationship between GCG on LPD performance. The research population was 50 LPD in Penebel, Tabanan. The sample was determined by the nonprobability sampling method with a purposive sampling technique, obtained as many as 25 LPD. The data are analyzed using path analysis. The analysis shows that GCG has a positive effect on LPD performance. GCG has a positive effect on team-oriented organizational culture. Team-oriented organizational culture has a positive effect on LPD performance. Team-oriented organizational culture mediates a part of the influence of GCG on LPD performance. Keywords: Good Corporate Governance; Team-Oriented Organizational Culture; Performance of Lembaga Perkreditan Desa.